2009
DOI: 10.1186/1476-4598-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic effect of iodine in mammary cancer: participation of 6-iodolactone (6-IL) and peroxisome proliferator-activated receptors (PPAR)

Abstract: Introduction: Studies in mammary cancer demonstrated that moderately high concentrations of molecular iodine (I 2 ) have a antiproliferative and apoptotic effect either in vivo as in vitro, however the cellular intermediated involved in these effects has not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 32 publications
(38 reference statements)
7
45
0
2
Order By: Relevance
“…In extrathyroid tissues, iodine plays an important role in the redox balance, either by free radical competition or indirectly inducing antioxidant enzymes, mediated by PPAR-gamma transcription factor activated by iodolactones. This ligand has been reported as iodine mediator [12,13,15,16,20,21]. Adequate iodine supplement is important for normal pregnancy, as iodine deficiency has been associated with oxidative stress and pregnant complications such as preeclampsia [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In extrathyroid tissues, iodine plays an important role in the redox balance, either by free radical competition or indirectly inducing antioxidant enzymes, mediated by PPAR-gamma transcription factor activated by iodolactones. This ligand has been reported as iodine mediator [12,13,15,16,20,21]. Adequate iodine supplement is important for normal pregnancy, as iodine deficiency has been associated with oxidative stress and pregnant complications such as preeclampsia [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…In the thyroid gland, intracellular iodine concentration plays an important role in redox balance by modulating hydrogen peroxide generation [8,9] and thyroid iodine deficiency induced intracellular production of reactive oxygen species (ROS) that stabilizes HIF-1α protein and then the expression and secretion of vascular epithelial growth factor (VEGF) for novel blood vessels [10]. It has been proposed that in thyroid and extrathyroid tissues, iodolipids are the mediators of iodine properties, through PPAR-gamma activation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer models, it has been shown that iodine supplementation inhibits expression of the VEGF and uPA genes (13,14). Our study shows that none of the TRAMP mice (control or iodine supplemented) developed a phenotype of The amount of mono-and oligo-nucleosomes was determined by ELISA.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 88%
“…This result could be explained by a strong inactivation of the p53 pathway by TAG antigens. for peroxisome proliferator-activated receptors (12,13,(18)(19)(20). There is evidence that prostate epithelium is an iodine-responsive target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation